KOMPETENCJE CYFROWE PRZYSZŁYCH NAUCZYCIELI JĘZYKÓW OBCYCH I ICH POTENCJALNY WPŁYW NA PLANOWANIE PROCESU DYDAKTYCZNEGO - Maziarz, Magdalena (Neofilolog, 2020)
This article and the study it describes present the results of research on the general level of digital competence of students in the teaching specialization in the context of preparation for the teacher profession and the Council of the European Union recommendation of 22 May 2018 on key competencies for lifelong learning. The results of the research are compared with publicly available reports on the digital competencies of Poles and with the European Media Literacy Standard for Youth Workers (EMELS).